2019
DOI: 10.1177/1010539519872642
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Internet Addiction and Perceived Parental Protective Factors Among Malaysian Adolescents

Abstract: Parental protective factors do play an important role in preventing Internet addiction. A self-administered questionnaire was used to measure health risk behaviors among Malaysian adolescents. The prevalence of Internet addiction was significantly higher among adolescents with perceived lack of parental supervision (30.1% [95% confidence interval (CI) = 28.7-31.4]) and lack of parental connectedness (30.1% [95% CI = 28.5-31.7]), compared with their counterparts. Adolescents who perceived a lack of parental sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
17
0
1
Order By: Relevance
“…These include parenting styles/parental rearing styles, parenting patterns, parental attitudes, internet parenting styles, parental mediation, parental bonding, parent–child relationship, parent–child attachment, parental control, parent–child communication, interparental conflict and parent–child conflict, parental monitoring, family functioning, parental norms, parental supervision, parental involvement with child computer use, parental neglect, child maltreatment, and family dysfunction. Studies have identified positive association of PUI in children with parenting factors such as parenting styles with poor warmth and excessive control, 52, 55, 57, 76, 85, 94, 98, 103, 104, 110 poor parent–child communication, 60 poor parent–child attachment, 50, 55, 59, 61, 6365, 70, 72, 76, 77, 79, 86, 90,92,93,97,100,106,109,115 restrictive mediation of internet use, 53, 58, 66, 79, 95, 100, 105, 108, 113, 116118 poor parent–child bonding, 54, 59, 62, 84, 101, 114 higher/poor parental control, 50, 56, 61, 102 paternal behavioral control, 56, 102 maternal psychological control, 56, 61 increased interparental conflict, 51, …”
Section: Resultsmentioning
confidence: 99%
“…These include parenting styles/parental rearing styles, parenting patterns, parental attitudes, internet parenting styles, parental mediation, parental bonding, parent–child relationship, parent–child attachment, parental control, parent–child communication, interparental conflict and parent–child conflict, parental monitoring, family functioning, parental norms, parental supervision, parental involvement with child computer use, parental neglect, child maltreatment, and family dysfunction. Studies have identified positive association of PUI in children with parenting factors such as parenting styles with poor warmth and excessive control, 52, 55, 57, 76, 85, 94, 98, 103, 104, 110 poor parent–child communication, 60 poor parent–child attachment, 50, 55, 59, 61, 6365, 70, 72, 76, 77, 79, 86, 90,92,93,97,100,106,109,115 restrictive mediation of internet use, 53, 58, 66, 79, 95, 100, 105, 108, 113, 116118 poor parent–child bonding, 54, 59, 62, 84, 101, 114 higher/poor parental control, 50, 56, 61, 102 paternal behavioral control, 56, 102 maternal psychological control, 56, 61 increased interparental conflict, 51, …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that male college students have a greater possibility of developing internet addiction than females (36)(37)(38)(39)(40). Male students exhibit highly addictive patterns toward internet gaming and are more likely to indulge in the internet when they lack parental supervision (41,42). Compared with internet addiction in female group, internet addiction in male group has greater association with school burnout (43).…”
Section: Introductionmentioning
confidence: 99%
“…Among our results, we find that education of adolescent children in privacy highly predicts better life satisfaction, lower alcohol use, and lower internet dependence. Similarly, Awaluddin et al (2019) found that, when parents respect their children's privacy, they are less prone to internet addiction.…”
Section: Association With Adolescent Outcomesmentioning
confidence: 95%
“…This is especially relevant during adolescence, when many new relations with others are established, both online and face-to-face, and because this is a difficult period to tackle (Zou and Wu, 2019). The study of this issue is critical, as respect for privacy is a family protective factor against addictions (Awaluddin et al, 2019).…”
Section: Parental Competence and Adolescencementioning
confidence: 99%